Systemic Bactericidal Complement in Human Cardiomyopathies: Revisiting Approach - Shnawa, Ibrahim M S; Abdurazak, Mohamed M; Alameidi, Baha H H (British Journal of Healthcare and Medical Research, 2026)
Cardiac diseases are of common prevalence among age human beings. In a clinical setting, the cardiologist of working team at Hilla Mergan Teaching Hospital, diagnose 23 cardiomyopathy test patients whom complained inflammatory-infectious manifestations in continuum with ageing processes. Five normal aged and five normal adulthood were the controls. The test and control groups were enrolled in blood collection with heparin for bactericidal assay. The heparinized one in tenth diluted blood samples were inoculated with fresh diluted E coli culture suspensions. The inoculated blood samples were incubated for 10,20 and 40 minutes at 37C.Then streaked onto nutrient agar plates and incubated for an overnight period in 37C.To score bactericidal activity onto the streak line; confluent growth means no action, weak growth means hypoactive and no growth means active bactericidal complement. Complement bactericidal activity patterns in cardiomyopathy patients were as; inactive ,hypoactive and active. The nature of this bactericidal activity was found to be dependent on the initial blood-bacteria interaction time at 37C as the time passed from 10 to 40 min. Nine out of the 23(39.13%) test patient have shown inactivity up to 40 min incubation. Fourteen out of the 23(60.7%) were expressing various grades of bactericidal activity. Complement inactivity can be attributed to; consumption of complement in immune-pathogenesis of the cardiac disease, ageing and/ or infection induced complement suppressive effects. Complement hypoactivity may be due to the cardiomyopathy and /or ageing.